Seneca's Saturnalia: the exception to the rules and the rules of exception - Winter, Kathrin (Maia, 2024)
Purchase online the PDF of Seneca's Saturnalia : the exception to the rules and the rules of exception, Winter, Kathrin - Morcelliana - Article